PS4:86 Obstetric and neonatal outcomes in systemic lupus erythematosus: a population-based register study. (21st March 2018) - Andersen, LS; Bliddal, M; Andersen, LL; Voss, A
Abstract : Introduction: In women with systemic lupus erythematosus (SLE) pregnancies may be negatively affected by disease activity and medical treatment. Increased frequencies of adverse outcome including preterm delivery and perinatal morbidity/mortality have been reported. However, different frequencies are reported from different studies. Aim and hypothesis: Utilising national health registers we want to investigate maternal and fetal outcomes in Danish pregnant SLE patients compared to outcomes in the background population. Methods: The outcome of pregnancies in Danish SLE patients in 1997–2016 is studied utilising healthcare-registries (the Danish National Patient Registry (NPR) and the Medical Birth Register (MBR)) and trends are described. Study population and material: All females with a diagnosis of SLE in the study period are identified from the NPR (ICD-8 and ICD-10 diagnoses of SLE). The outcome of all pregnancies (routinely registered in NPR and MBR) is compared to the outcome in an age-matched cohort of pregnant women without SLE (each SLE patient is matched with 20 females from the background population). Data about infants are retrieved from the MBR Statistics: Using logistic regression we will examine if risk of adverse maternal and fetal outcome is higher in women with SLE than in women without SLE, by calculating crude and adjusted odds ratios Results: Frequencies of adverse maternal outcomes including preeclampsia, preterm delivery and Caesarean section, and adverse infant outcome including asphyxia, growth retardation and low Apgar score will be presented. Crude and adjusted odds ratios will be calculated comparing pregnancies in SLE females with pregnancies of non-SLE females. Data are at present being retrieved from the Danish authorities and subsequent data analysis is expected to be completed December 2017. Approximately 800 women with SLE are expected to be included in the study.